A multilevel investigation of leader–member exchange differentiation’s consequences: A moral disengagement perspective - Al-Atwi, Amer Ali; Alshaibani, Elham; Bakir, Ali; Shoaib, Haneen M.; Dahlan, Mohanad (Frontiers in Psychology, 2022)
We examine the effects of leader–member exchange (LMX) differentiation on team members’ outcomes (customer-oriented constructive and destructive deviant behaviors) by using team moral disengagement as a psychological mechanism mediating this relationship and LMX differentiation bases (i.e., performance and personal liking) moderating the relationship. Analysis of multilevel data collected from 289 frontline employees organized into 76 finance-related customer service teams shows that LMX differentiation significantly reduced team moral disengagement only when the performance basis was high, and that the negative relationship between LMX differentiation and team moral disengagement was significant only when the personal liking basis was low. Furthermore, we found that the LMX bases moderated the indirect effect of LMX differentiation on team members’ outcomes through team moral disengagement. The findings advance team moral disengagement as a novel mechanism for cross-level relationship between LMX differentiation and team members’ outcomes at the individual level, and project differentiation bases as a condition under which LMX differentiation unpacks the reasons for team members’ favorable or unfavorable responses. They reveal LMX differentiation as a complex and multifaceted phenomenon, whose essence can only be understood if examined from multiple levels. We also contribute to the literature by revealing the cognitive pathway through which LMX differentiation may be associated with team members outcomes.